Towards energy transition: conjoint assessment of large-scale PV system performance and interconnection impacts in isolated microgrid - Zen L. Chai; S.P Ang; A. Khalil; M. A. Salam; W. Z. Wan Hasan; William Voon (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2020)
Environmental, energy security and electricity demand concerns stimulate solar-grid integration. However, intermittent, non-dispatchable PV characteristics may challenge passive grid operation. This paper contains the comprehensive planning and assessment of a 2 MWp CdTe-based PV system deployment proposed for hybrid operation in an isolated 11 kV 10-bus microgrid in Brunei. The presented approach combinedly assesses PV system performance and scenario-based interconnection impacts based on a detailed PV system model considering deployment conditions. Various interconnection points with multiple sets of feeder-specific measured load profiles are examined. Results show the PV system designed for maximum annual generation achieves performance ratio of 90.6%. While time-series power flow assessment reveals grid operation enhancement, there are concerns at times of generation-demand mismatch requiring proper genset sequencing and reactive power management. Meanwhile, faster relay operating time and reverse fault current are demonstrated in existing protection scheme. Dynamic grid stabilities are preserved in various generation intermittency and loss events, including the most challenging condition of further inertia and spinning reserve reduction reaching a frequency of 96.02%. Finally, optimal interconnection point fulfilling multi-objectives on losses, voltage profile and line reserve capacity is identified. The findings indicate a good prospect of the synergy for advancing energy transition. The analysis could facilitate RE planning and policymaking.